2017
DOI: 10.5455/njppp.2017.7.0724521072017
|View full text |Cite
|
Sign up to set email alerts
|

State of lipid peroxidation and endogenous intoxication under non-small-cell lung cancer

Abstract: Background: The problems of optimizing the methods of diagnosis and predicting the course of lung cancer occupying a leading position in the structure of cancer are still relevant. Aims and Objectives: To establish the patterns of changes in the parameters of endogenous intoxication and lipid peroxidation processes in the saliva of patients with non-small-cell lung cancer (NSCLC) depending on the histological type of a tumor. Materials and Methods: A total of 505 people took part in the case-control study: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 22 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…It was shown that the level of diene conjugates increased with lung cancer compared to a control group [65,66]. The level of secondary products against the background of lung cancer rose regardless of the histological type of tumor [67,68] (Supplementary Table S1). Increasing the level of Schiff bases is an adaptive process aimed to eliminate more toxic metabolite MDA from the cells.…”
Section: Discussionmentioning
confidence: 97%
“…It was shown that the level of diene conjugates increased with lung cancer compared to a control group [65,66]. The level of secondary products against the background of lung cancer rose regardless of the histological type of tumor [67,68] (Supplementary Table S1). Increasing the level of Schiff bases is an adaptive process aimed to eliminate more toxic metabolite MDA from the cells.…”
Section: Discussionmentioning
confidence: 97%